THE INFLUENCE OF THE IMPLEMENTATION OF PROBLEM-BASED LEARNING AND STEM ON THE HOTS ABILITY OF HIGH SCHOOL’S STUDENTS IN SURABAYA - Amalia Chamidah (IAIN Ambon, 2023)
Problem-based learning (PBL) is one of the innovative learning models that provides learning opportunities for students to be directly involved in learning processes the real life reality. This study to determine the significance of the application of STEM-based PBL on the HOTS ability of Hang Tuah 4 High School students Surabaya. The sample of this research is 17 students of class X SMA Hang Tuah 4 Surabaya in the academic year 2021-2022. Data were collected through tests and documentation conducted by the researcher together with the mathematics teacher when teaching SPLDV. Data were analyzed using SPSS 25.0 for windows. The result is that the application of STEM-based PBL has an influence on the HOTS ability of students at Hang Tuah 4 High School Surabaya. For this reason, it is recommended for mathematics teachers to apply STEM-based PBL to familiarize students with HOTS thinking.